Electrolysis on a Chip with Tunable Thin Film Nanostructured PGM Electrocatalysts Generated from Self‐Assembled Block Copolymer Templates. Issue 25 (14th May 2021) - Bhattacharya, Deepra; Kole, Subarna; Kizilkaya, Orhan; Strzalka, Joseph; Angelopoulou, Polyxeni P.; Sakellariou, Georgios; Cao, Dongmei; Arges, Christopher G.
Abstract: Self‐assembled block copolymers are promising templates for fabricating thin film materials with tuned periodic feature sizes and geometry at the nanoscale. Here, a series of nanostructured platinum and iridium oxide electrocatalysts templated from poly(styrene)‐ block ‐poly(vinyl pyridine) (PS b PVP) block copolymers via an incipient wetness impregnation (IWI) pathway is reported. Both nanowire and nanocylinder electrocatalysts of varying feature sizes are assessed and higher catalyst loadings are achieved by the alkylation of the pyridine moieties in the PVP block prior to IWI. Electrocatalyst evaluations featuring hydrogen pump and water electrolysis demonstrations are carried out on interdigitated electrode (IDE) chips flexible with liquid supporting electrolytes and thin film polymer electrolytes. Notably, the mass activities of the nanostructured electrocatalysts from alkylated block copolymer templates are 35%–94% higher than electrocatalysts from non‐alkylated block copolymer templates. Standing cylinder nanostructures lead to higher mass activities than lamellar variants despite their not having the largest surface area per unit catalyst loading demonstrating that mesostructure architectures have a profound impact on reactivity. Overall, IDE chips with model thin film electrocatalysts prepared from self‐assembled block copolymers offer a high‐throughput experimental method for correlating electrocatalyst nanostructure and composition to electrochemical reactivity. Abstract : Nanostructured platinum group metal thin films of tunable feature size and morphology templated from self‐assembled block copolymers are tested for electrochemical hydrogen oxidation/hydrogen evolution and water‐splitting activity on interdigitated electrode chips.